GAMBARAN PENGETAHUAN DAN KEBERADAAN BAKTERI ESCHERICHIA COLI PADA MINUMAN ES TEH DI DESA GONILAN UNIVERSITAS MUHAMMADIYAH SURAKARTA - Isnaini Septiyana; Windi Wulandari (Jurnal Ners, 2025)
Every day humans need water to survive. Water is the main ingredient in making tea, juice and other bevereges. Therefore to prevent health problems, drinking water must meet all health standards, including chemical, physical, radioactive and microbiological. Microbial contamination can occur due to management that does not comply with hygiene standards, environmental conditions, cleanliness of equipment, management behavior, processing space, and quality of raw materials. One indicator of drinking water quality and safety is the presence of fecal coliform bacteria including Escherichia coli. The purpose of this study was to describe the knowledge and identify the presence of Escherichia coli bacteria in iced tea in Gonilan village UMS. The research design is descriptive to describe the knowledge of trade related to sanitary hygiene and determine the prevalence of Escherichia coli bacteria in iced tea. The sample of this study were 20 iced tea traders and 20 cup packaged iced tea. Accidental sampling was the method used for sampling. Analisis of the result using univariate test and comparing the result of Escherichia coli test with PERMENKES No. 2 of 2023. The results showed that of the 20 samples tested, 2 iced teas (10%) were positive for Escherichia coli. The knowledge of traders about sanitary hygiene is good as seen from 20 samples of ice tea tested only 2 iced teas (10%) were positive for Escherichia coli.